Peripheral vascular endothelial growth factor changes after transcranial magnetic stimulation in treatment-resistant depression. Issue 16 (4th November 2020) - Fukuda, Andrew M.; Hindley, Lauren E.; Kang, Jee Won Diane; Tirrell, Eric; Tyrka, Audrey R.; Ayala, Alfred; Carpenter, Linda L.
Abstract : Objectives: To determine if vascular endothelial growth factor (VEGF) changes with transcranial magnetic stimulation (TMS) in treatment-resistant major depressive disorder (MDD). Methods: Serum from a naturalistic population of 15 patients with MDD was collected at baseline and after standard TMS treatment. VEGF concentration was determined via ELISA. Inventory of Depressive Symptomatology Self Report and Patient Health Questionnaire were used as a measure of depression symptom severity, clinical response and remission. Mann–Whitney U and Kendall's Tau Correlation were used for continuous variables. Results: VEGF increased from pre- to post-TMS (+30.3%) in remitters whereas VEGF decreased in non-remitters (−9.87%) ( P < 0.05). This same pattern was observed when comparing mean %change in VEGF between responders (+14.7%) and non-responders (−14.9%) ( P = 0.054). Correlation was present between change in VEGF concentration (baseline to post) and change in Inventory of Depressive Symptomatology-Self Report at Tx30 ( r = −0.371, P < 0.054), reflecting greater increases in VEGF linked to greater improvement in depressive symptoms following the standard 6-week course of TMS. Conclusion: Patients with a successful treatment with TMS had significantly greater increase in VEGF from baseline to after treatment compared to non-responders/non-remitters and a larger increase in VEGF was associated with greater improvement in depressive symptoms after TMS. This is the first report examining VEGF levels in depressed patients receiving TMS. This study provides correlative data supporting further investigation into VEGF's role as an important mediator in the processes underpinning TMS' antidepressant effects and as a potential biomarker of clinical outcomes.